Prospective evaluation of the International Study Group for liver surgery definition of post hepatectomy liver failure after liver resection: an international multicentre study - Sultana, Asma; Büchler, Markus W. (HPB, 2018)
Background: The International Study Group for Liver Surgery (ISGLS) definition of post hepatectomy liver failure (PHLF) was developed to be consistent, widely applicable, and to include severity stratification. This international multicentre collaborative study aimed to prospectively validate the ISGLS definition of PHLF. Methods 11 HPB centres from 7 countries developed a standardised reporting form. Prospectively acquired anonymised data on liver resections performed between 01 July 2010 and 30 June 2011 was collected. A multivariate analysis was undertaken of clinically important variables. Results: Of the 949 patients included, 86 (9%) met PHLF requirements. On multivariate analyses, age ≥70 years, pre-operative chemotherapy, steatosis, resection of >3 segments, vascular reconstruction and intraoperative blood loss >300 ml significantly increased the risk of PHLF. Receiver operator curve (ROC) analysis of INR and serum bilirubin relationship with PHLF demonstrated post-operative day 3 and 5 INR performed equally in predicting PHLF, and day 5 bilirubin was the strongest predictor of PHLF. Combining ISGLS grades B and C groups resulted in a high sensitivity for predicting mortality compared to the 50-50 rule and Peak bilirubin >7 mg/dl. Conclusions: The ISGLS definition performed well in this prospective validation study, and may be the optimal definition for PHLF in future research to allow for comparability of data.
Published online: 26 December 2017
Gesehen am 15.06.2018